Espaços, equipamentos de lazer e acessibilidade: o caso de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This research addresses the issue of accessibility: more specifically in leisure facilities in the city of Manaus; however, it is aimed at a target audience: the visually impaired or, as we call it at work, “people with visual limitations in a social context”. Research has a diversity of methodologies: such as bibliographical, field research with a more qualitative nature for analysis; completely blind people or those with low vision were interviewed to find out about their perception of the leisure facilities we visit: cinema, theater, museum, physical-sports space, to discover accessibility patterns in these places, how to understand the autonomy of people with limitations visuals in a social context. The intention of the spaces with the people interviewed is to understand the reception of leisure. Leisure and accessibility is still a topic little explored by the academic environment, as a result, we gave voices to the present and the past of Manaus: to find out if there was a change for people with visual limitations in a social context who lived in the second half of the century XX the capital of Amazonas and the leisure equipment belonging to it or if the panorama remains the same, even with a new social grammar in force, with new technologies and new leisure equipment. For this, the point of view was not limited to researchers and interviewees alone, as there was a voice for people who work in leisure facilities and State institutions. Keywords: Leisure, Accessibility, City.
Keywords: .; .; .; CIENCIAS SOCIAIS APLICADAS; CIENCIAS HUMANAS; Lazer; Acessibilidade; Cidade